Polymer Films for Photovoltaic Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Reprints of Polymers Special Issue entitled "Polymer films for photovoltaic applications", which covers all fields related to polymer films for photovoltaic applications, but special attention will be given to the following aspects:- The synthesis and suitable modification of polymer structure, to obtain polymer thin films for PV devices;- The influence of film deposition (thermal vacuum evaporation (TVE), chemical vapor deposition (CVD), spin coating, spray, etc.) on the properties of polymer films;- The thermo-optical properties of polymer thin films and blends of polymer films, as potential parts of PV systems;- The influence of doping or protonation of polymer thin films and blend polymer films on their properties;- Polymer thin films as active layers in PV solar cells—correlation of chemical structure and PV properties;- BHJ solar cells with polymer blends films—the choice of blend film composition to obtain the best PV parameters.